PENGARUH MEDIA SOSIAL DAN SELF EFFICACY TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IPS SMA NEGERI 1 KOTA KUPANG - Rostanti, Nofi; Abolladaka, Jacob; br. Simanungkalit, Erika Feronika (Universitas Nusa Cendana, 2024)
This research was conducted at SMA Negeri 1 Kupang City, Kupang, with the title The Influence of Social Media and Self-Efficacy on Economic Learning Outcomes of Class XI Students. The type of study used is quantitative with a causal associative approach. The sample in this research was 108 students taken using probability sampling techniques. Observation, interviews, questionnaires, and documentation are data collection methods. In this research, classical instrument and assumption tests were carried out and it was declared feasible so it was continued in multiple linear regression. The calculation results were proven to be valid and reliable for each questionnaire statement item. The statistical requirements test shows that the data is normal, linear and there is no heteroscedacity. The results of this test show that a significant positive influence was found between X1 and X2 includes social media (X1) with a calculated f value of 14.861 exceeding the f table of 4.81 with a significant level of 0.000, The influence of social media and self-efficacy (X2) are both positive, with a calculated t value of 2.063 exceeding the t table of 1.659 and a significance level below 0.05. Keywords : Social Media, Self Efficacy, Learning Result.